Cognitive Load and Working Memory in Sharaf Rule Acquisition - Ismail, Holil; Yul, Widiya; Andrian, Riko (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2025)
This study investigates cognitive load and rule acquisition in sharaf (Arabic morphology) learning, with particular attention to the role of working memory among third-semester students of the Arabic Language Education Program at IAIN Kerinci. Employing a qualitative case study design, data were collected through in-depth interviews with 10 students and participatory observation in sharaf classes. Thematic analysis revealed four primary challenges: (1) the linguistic complexity and irregularity of morphological patterns that burden memory, (2) limited working memory capacity that constrains the recall and application of rules, (3) pedagogical gaps caused by lecture-dominated methods with minimal student engagement, and (4) differences in students’ educational backgrounds that affect comprehension. The study further identified effective strategies for reducing cognitive load, including material simplification with visual aids, structured and contextual repetition, task-based learning, and metacognitive training. These findings highlight the importance of adaptive teaching approaches aligned with students’ cognitive capacities to enhance Arabic language instruction.